A case study for the assessment of fuel savings using speed optimization. (15th April 2023) - Taskar, Bhushan; Sasmal, Kaushik; Yiew, Lucas J.
Abstract: Potential fuel savings using a speed optimization algorithm have been studied for two case vessels in four different seasons at three ship speeds. Up to 6% fuel savings were observed. It was found that the savings are higher in seasons with a higher likelihood of severe weather conditions. Larger savings were observed at lower ship speeds which means, slow steaming combined with speed optimization can obtain even higher fuel savings and emission reduction. In addition to fuel saving, speed optimization can also ensure the timely arrival of vessels in harsh weather conditions. A methodology has been presented to optimize ship speed without altering the route; subject to constraints that voyage time is not exceeded and engine operating point is within the engine limits. A detailed analysis of wind and wave parameters on a transpacific route in four seasons has been presented to supplement the voyage performance analysis in different metocean conditions. Highlights: Up to 6% savings were observed using speed optimization. Slow steaming combined with speed optimization has greater potential. Greater savings observed in heavy weather conditions. Speed optimization also helps to avoid delay in bad weather.